ANALISIS KOREKSI FISKAL ATAS LAPORAN KEUANGAN KOMERSIAL PADA PT CITRA TUMBUH LESTARI TAHUN PAJAK 2013 - B. Soehakso Notohatmodjo (AKSES: Jurnal Ekonomi dan Bisnis, 2015)
The study aims to look at the PT. Citra Tumbuh Lestari which is located in Petojo Selatan I No.40, Central Jakarta related to compliance in tax laws applicable to the fiscal correction in thecommercial financial report in 2013 along with fiscal correction described. The method used inthis research is descriptive method; aims to describe and explain the data or events sentencesexplanation. Data obtained by conducting data collection that is interview, documentation, andliterature study. The collected data were analyzed by descriptive analysis of the comparativemethod. Conclusions from the analysis of the data based on research results CommercialFinancial Statements PT Citra Tumbuh Lestari contained positive fiscal correction where thereare several accounts expense recognized in accordance with Financial Accounting Standards, butaccording to the Tax Accounting should not be recognized as an expense. Based on the calculationof the total correction of Rp 340 884 894 positive and negative fiscal correction Rp 38.543.829.As a result of the fiscal correction is then an increase in the commercial profit of Rp2.645.998.935,- to Rp 2.948.340.000,- or profit rose 11.42% in accordance with the rules-basedfiscal correction Tax Act.Keywords: Fiscal Correction, Commercial Financial Statements